A Contrastive Linguistic Study of "Hakase no aishita sūshiki" (Sp. tr. "La fórmula preferida del profesor") by Yoko Ogawa - Ikuno, Yoko (Estudios de Traducción, 2017)
The works of the Japanese novelist Yoko Ogawa have been translated into different languages, and it is worth pointing out the translations to Spanish of novels like La fórmula preferida del profesor (Ogawa 2008) or La niña que iba en hipopótamo a la escuela (Ogawa 2011) and so on. The aim of this paper is to analyze some of the problems regarding the semantic ambiguity, the omission of onomatopoeias and the difficulty in interpreting the original text that we can find in the Spanish translation of Hakase no aishita sūshiki (tr. La fórmula preferida del profesor). This article presents a theoretical linguistic analysis that explores in depth the asymmetries between lexical categories in Japanese and Spanish.